Capital structure and regulation in US local telephony: an exploratory econometric study - Marcelo Resende (Center for Economic Studies and ifo Institute (CESifo), 2009)
The paper aims at empirically investigating the relationship between regulation and the capital structure of the regulated firm, A key aspect of the referred relationship pertains a leverage effect according to which debt could be increased as a response to previous physical capital investment with an ultimate goal of inducing higher rates. Theoretical models like Spiegel and Spulber [1997, RAND Journal of Economics] highlight that effect. The present paper considers a panel data set of local exchange carriers-LECs in the U.S. and investigate Granger causality between changes in long-term debt (NDEBT) and gross investment (INV) in physical capital. The evidence accruing from a dynamic panel data estimation indicates an uni-directional causality from INV to NDEBT and therefore is, to a large extent, consistent with a leverage effect and with the notion that the size of the firms investment project can impose a restriction on the amount of new debt. The result prevails independent of a control variable that indicates the regulatory regime.
Keywords: G32; L51; L96; 330; regulation; capital structure; dynamic panel data; Telefongesellschaft; Gemeinde; Kapitalstruktur; Investition; Telekommunikationspolitik; Panel; USA